2018
DOI: 10.1186/s40665-018-0038-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between changing climate and body condition over decades in two southern hemisphere passerine birds

Abstract: Background: Climate change presents considerable challenges for endotherms because they must maintain high, relatively constant body temperatures across a range of environmental conditions to ensure survival and optimise performance. Individuals exposed to changing weather must manage energy and water allocation to maintain thermal homeostasis, with consequences for body condition, and hence there is potential for selection because body condition is strongly linked to fitness. Understanding how weather drives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…Previous studies have found that body condition increases winter survival Grubb 2002, Danner et al 2013) and can interact with temperature to modify an animals' sensitivity to extreme weather (Williams et al 2014, Gardner et al 2018. We found some support that body condition influenced winter survival, but not an individuals' sensitivity to extreme winter weather.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Previous studies have found that body condition increases winter survival Grubb 2002, Danner et al 2013) and can interact with temperature to modify an animals' sensitivity to extreme weather (Williams et al 2014, Gardner et al 2018. We found some support that body condition influenced winter survival, but not an individuals' sensitivity to extreme winter weather.…”
Section: Discussionsupporting
confidence: 61%
“…, Gardner et al. ). We found some support that body condition influenced winter survival, but not an individuals’ sensitivity to extreme winter weather.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Variations in seasonal weather patterns and the occurrence of extreme weather events such as droughts, floods, and heatwaves are among the primary drivers of variation in individual success in vertebrates, influencing reproduction and survival both directly and indirectly, often via effects on resource availability (Harrison et al, 2011). To date, most research on the within and between season effects of weather patterns and extreme events has focused on the influence within an annual cycle (Saino et al, 2011;Laplante et al, 2019) of (a) conditions during early development on individual success as a nestling (Pérez et al, 2008;Auer and Martin, 2017;Ospina et al, 2018), fledgling (Blomberg et al, 2014;de Zwaan et al, 2019), or adult (Porcelli et al, 2016;Hsu et al, 2017;Marshall et al, 2017) and (b) seasonal weather conditions on body mass (Loison and Langvatn, 1998;van de Pol et al, 2016), behavior (Akresh et al, 2019;Rauber et al, 2019), survival (Berryman and Lima, 2006;Gardner et al, 2017Gardner et al, , 2018Woodworth et al, 2017;Chiffard et al, 2019), and reproductive investment (Clutton-Brock et al, 1991;Monteuil-Spencer, 2017).…”
Section: Introductionmentioning
confidence: 99%